И.ЮСУПОВТЫҢ ПОЭМАЛАРЫНДА ТЕҢЕЎЛЕР - Ержанова, Д.К. (FAN va JAMIYAT, 2019)
The article is devoted to the study of using the stylistic device simile in the poems of the great People’s poet I.Yusupov his skill in using simile. The author also studies the role of the poet’s works in the development of the modern Karakalpak literary language.